Does Board Age Diversity Influence Shareholder Value Creation? Empirical Evidence from South African Listed Non-Financial Companies - Zvinowanda, Douglas (International Journal of Economics and Financial Issues, 2026)
This study investigated the influence of board age diversity (BAD) on the shareholder value creation (SVC) of South African non-financial companies listed on the JSE. A quantitative quasi-experimental design was used. The data collection sources included integrated annual reports, the Who Owns Whom database and the Osiris database. The study measured board age diversity using the Blau index (BI_BAD), average age (AVE_ABM), standard deviation(SD_ABM), coefficient of age variation (CV_ABM) for board members, and dummy variables for age diversity categories. The proxies of the SVC included standard market value added (SMVA), market-to-book ratio (MTB) and Tobin’s Q (TBQ). A fixed effects model was employed to test the hypotheses. The curvilinear quadratic models revealed that all BAD measures positively and negatively impacted all SVC measures, highlighting a U-shaped or an inverted U-shaped effect. The empirical findings suggest that moderate levels of age diversity contribute positively to shareholder value, while very low or high BAD levels may be less beneficial. The statistical results support the multi-theoretical perspective that BAD has a double-edged sword effect. These results offer important insights for corporate governance practices, highlighting the strategic role of board composition in enhancing shareholder value creation in emerging markets. Also, the results highlight the importance of balanced BAD for optimising shareholder value in emerging markets.